2012
DOI: 10.1126/science.1215065
|View full text |Cite
|
Sign up to set email alerts
|

Massive Phytoplankton Blooms Under Arctic Sea Ice

Abstract: Phytoplankton blooms over Arctic Ocean continental shelves are thought to be restricted to waters free of sea ice. Here, we document a massive phytoplankton bloom beneath fully consolidated pack ice far from the ice edge in the Chukchi Sea, where light transmission has increased in recent decades because of thinning ice cover and proliferation of melt ponds. The bloom was characterized by high diatom biomass and rates of growth and primary production. Evidence suggests that under-ice phytoplankton blooms may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
597
2
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 670 publications
(624 citation statements)
references
References 14 publications
22
597
2
3
Order By: Relevance
“…The length scale of melt pond variability on the floe was 9.3 m as determined by variogram analysis of the classified aerial image (range value). The thick ice, the considerable surface layer, the geographic position close to Greenland and the timing early in the melting season are the reason for the low light transmittances when compared to other studies from other regions or later in the summer [ Arrigo et al ., 2012; Nicolaus et al ., 2012]. …”
Section: Resultsmentioning
confidence: 99%
“…The length scale of melt pond variability on the floe was 9.3 m as determined by variogram analysis of the classified aerial image (range value). The thick ice, the considerable surface layer, the geographic position close to Greenland and the timing early in the melting season are the reason for the low light transmittances when compared to other studies from other regions or later in the summer [ Arrigo et al ., 2012; Nicolaus et al ., 2012]. …”
Section: Resultsmentioning
confidence: 99%
“…Nutrient depletion near the surface is observed during each summer period, when the light limitation decreases and the sea ice breaks up, allowing phytoplankton blooms to spread along the base of the sea ice (Arrigo et al, 2012). Remarkably, surface N/P ratios were low in both basins and never reached the expected Redfield ratio (16/1) (Fig.…”
Section: Pml and Haloclinementioning
confidence: 99%
“…It should be noted that the similarity could be due to biased seasonal coverage by field studies in ice-free waters, introducing more measurements collected in late summer and fall (i.e., September), thus lowering the ice-free iNPP average (not shown). Alternatively, the similarity in simulated iNPP values in ice-free and ice-influenced areas could result from the averaging of regional differences previously observed in field and satellite-derived NPP data [e.g., Arrigo et al, 2012;Hill et al, 2013;Ardyna et al, 2013] as well as in model simulations [e.g., Zhang et al, 2015]. Recently, Jin et al [2016] showed that simulated under-ice production is also regionally different (i.e., higher in the Arctic shelves, possibly due to enhanced nutrient supply) [Zhang et al, 2015], but not necessarily related to the recent decrease in sea ice concentration, especially in marginal ice zones.…”
Section: 1002/2016jc011993mentioning
confidence: 99%